Relapsing polychondritis-associated meningoencephalitis initially presenting as seizure: a case report and literature review - Zhang, Dan; Shi, Jiamin; Zhang, Xinhua; Wang, Jin; Shao, Yuquan (Frontiers in Neurology, 2023)
Background and purpose Relapsing polychondritis (RP) is a rare rheumatologic disorder that may affect the neurological system with various presentations. In this study, we present a case and summarize the clinical characteristics of RP-associated meningoencephalitis. Case presentation A 48-year-old man presented with first-ever seizures that were well controlled by valproate. Physical examination results were unremarkable, except for binaural deformation. The initial brain magnetic resonance imaging (MRI) without contrast and electroencephalogram (EEG) findings were normal. However, the patient subsequently developed recurrent fever, scleritis, headache, lethargy, and left arm paresis. Repeated brain MRI with contrast demonstrated increased enhancement of the pia mater and abnormal diffusion-weighted imaging (DWI) signals in the bilateral auricles. The cerebrospinal fluid (CSF) analysis showed 2 leukocytes/μL, 736.5 mg/L of protein, and no evidence of infectious disease or autoimmune encephalitis. Meningoencephalitis secondary to RP was considered. The patient's condition improved significantly and quickly with the administration of dexamethasone (10 mg per day). Oral methylprednisolone was continued, and the patient remained well without relapse during the 9-month follow-up period. Conclusion RP-associated meningoencephalitis is rare but fatal. Although symptoms vary, red or deformed ears remain the most common and suggestive features. Non-specific parenchymal changes and/or meningeal enhancement can be observed on brain MRI scans. CSF lymphocytic pleocytosis with mild protein elevation was observed in most patients.